Mauriac syndrome in an adolescent â case report: a rare complication of type 1 diabetes mellitus - Biana Moreira; Teresa Botelho Brito; Inês Fernandes; Susana Parente (Portuguese Journal of Pediatrics, 2025)
Introduction: Mauriac syndrome is a rare complication of type 1 diabetes mellitus associated with poor metabolic control, which is particularly rare since the introduction of intensive insulin therapy. It is characterized by hepatomegaly, dyslipidemia, growth failure, and delayed puberty. Case report: We present the case of a 14-year-old male with Mauriac syndrome, with poor metabolic control since his diagnosis of type 1 diabetes mellitus at age two, with further deterioration during adolescence due to insulin omission and consultation absenteeism. Early recognition of this syndrome is crucial, given its reversibility with appropriate glycemic control. Discussion: This case underscores the importance of a personalized approach to patient care, highlighting the challenges of therapeutic compliance during adolescence, which often necessitates a multidisciplinary team and a comprehensive understanding of the patient’s circumstances.